Biomedical applications of Aloe vera. (27th June 2019) - Gao, Yan; Kuok, Kit Ieng; Jin, Ying; Wang, Ruibing
Abstract: Over the last centuries, Aloe vera, a plant species belonging to the genus Aloe, have been extensively studied for various therapeutic activities, including anti-bacterial, anti-viral, anti-cancer activity, as well as immunoregulative and hepatoprotective properties, although some of these claimed efficacies are controversial as demonstrated by some of the recent studies. In spite of the intensive historic and recent use of this herb and its extracts in various areas, a well-balanced, systematic review seems crucial in order to gain in-depth comprehensive knowledge about this plant and to reflect and revive the use of Aloe vera in biomedical sciences. This review will focus on summarization of the pharmacological activities and clinical studies of Aloe and various extracts, as well as its extensive application in food chemistry, and will also discuss the future prospects of biomedical applications of this herb. Highlights: It is the first systematic review of the full spectrum of bioactivities of Aloe vera . Comprehensive overview of the clinical applications of Aloe vera is also provided, as well as the underlying mechanism. Quality control, preparations and current products of Aloe vera are discussed. The application of Aloe vera in food chemistry is discussed.